CORPUS RESEARCH ON HEDGES IN LINGUISTICS AND EFL JOURNAL PAPERS - Wang, Shih-Ping; Tatiana, Khunkhenova (UPI Press, 2016)
There has been a considerable increase in the number of studies on hedges that can help authors to reduce commitment and negotiate the meaning between the reader and the writer. This study examines hedging devices based on corpus-based analysis of 750 research articles (4,831,500 running words) extracted from 15 leading journals in the areas of linguistics and EFL. Wordsmith Tools 5.0 was used for identifying hedging devices. The frameworks of both Hyland (1998a, 2005) and Varttala (1998) were integrated to identify the functions of hedging devices. The results reveal that modal auxiliary hedging (44.9%) is found more than the other types, while the noun category is the least used (2.17%). However, the use of different syntactic features (personal or impersonal) when combined with epistemic lexical terms appeared to influence different interpretations of lexical hedging mainly regarding the politeness strategy. Additionally, it is the authors' responsibility to hedge their own propositions. Learners should know the rules of hedges to distinguish real facts and findings from researchers' biased views and conclusions, and to use these markers accurately in their own works. The current study is practical for EFL learners as it discusses many types of hedges for familiarizing students with the appropriate use of hedging.